EVALUASI DAN DAMPAK PELAKSANAAN PROGRAM BANTUAN DANA BAGI HASIL CUKAI TEMBAKAU MADURA - Santoso, Pudji; -, Purwanto (MAPETA, 2010)
The aim of the research were 1) to find an information of the implementation of the funding program to the tobacco farmers group (where the funds was collected from the tobacco excise tax), 2) to formulate the alternatives of problem-solving during the implementation of the funding program to the tobacco farmers group, and 3) to find the impact of the funding program to the productivity and income of the tobacco farming. Data was collected in Sumenep and Pamekasan regencies, as the centre production of Madurese tobacco, during August - September 2009 using survey method. The results showed, that the funding program to the tobacco farmers group in Sumenep regency in 2009 was aimed for the arid and hilly land. This program was released as equipment assistance, capital assistance and guidance to the tobacco farmers group, while in Pamekasan regency, such program was implemented for organizing tobacco nursery. Problem faced in the implementation of this funding program in Sumenep and Pamekasan regencies was too late in disbursing of the funds. In Sumenep regency, this problem caused the late of the coming of pump water aid, whereas the tobacco plants needed to be watered. In Pamekasan regency, too late in disbursing of the funds resulted the implementation of the program such as preparation of the seed was delayed. Problem solving alternatives of the late in disbursing funds aid in the two regencies were collecting the capital from the group members or by borrowing the capital from the another fundsources. Funding program to the tobacco farmers group in Sumenep and Pamekasan regencies gave positive impact to the increasing of productivity and income of the tobacco farming.Keywords: Funding program, farmers group and Tobacco